Accounting Aid for Developing Countries. - Lowe, Howard D. (The Accounting Review, 1967)
Abstract This article focuses on the accounting aid for developing countries. The developing countries which constitute the majority in the world in both numbers and population are struggling to develop primary production to enable them to effectively utilize their resources, generate employment, and equitably distribute their wealth. The industrialization process in the United States and in Western Europe has been evolutionary in nature and has required several hundred years. During this time accounting, engineering, and other related professions have also developed through an evolutionary process both in terms of theory and procedures, and in terms of the number of people engaged in these professions. Some of the developing countries of the present day are attempting to avoid this long evolutionary process in their industrial development. By utilizing the organizational methods and technical knowledge they hope to achieve as much in terms of industrialization in a few decades as America and Western Europe